Histological Study of White Rats Kidney Following The Consumption of Obat Pahit From Riau Archipelago - Fitmawati Fitmawati; Agus Saputra; Titrawani Titrawani; Erwina Juliantari; Awal Prichatin Kusumo (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Obat Pahit from Lingga Malay ethnic is a traditional medicine which has believed by the local people to maintain the body stamina (immunomodulators and antioxidants). This study aimed to investigate the effect of Obat Pahit Potion on kidney histological structure of white male rats (Rattus norvegicus). This research was an experimental study with a Randomized Complete Block Design consisted of 15 treatments and 3 replications. The experiment groups consisted of control groups (Stimuno, distilled water, and CMC-Na 1%) and three treatment groups of Obat Pahit Potion (Kalan, SP4, Linau) with 4 different dosages. The samples of a kidney of white rats were prepared for histological observation using paraffin method and Hematoxylin-Eosin staining. The results of this study showed that three kinds of Obat Pahit with four different dosages showed the expansion of glomerular cells on kidney tissue. Damage that occurs in the kidneys is still in small amounts and normal range which is less than 25%. The results of this study provide information for the society that the consumption of Obat Pahit Potion will not cause toxicity effect on the kidney.